Real-world experience of using ciclosporin-A 0.1% in the management of ocular surface inflammatory diseases. Issue 8 (9th March 2021) - Deshmukh, Rashmi; Ting, Darren Shu Jeng; Elsahn, Ahmad; Mohammed, Imran; Said, Dalia G; Dua, Harminder Singh
Abstract : Purpose: To report the real-world experience of using topical ciclosporin, Ikervis, in the management of ocular surface inflammatory diseases (OSIDs). Methods: This was a retrospective study of patients treated with Ikervis for OSIDs at the Queen's Medical Centre, Nottingham, between 2016 and 2019. Relevant data, including demographics, indications, clinical parameters, outcomes and adverse events, were collected and analysed for patients who had completed at least 6 months follow-up. For analytic purpose, clinical outcome was categorised as 'successful' (resolved or stable disease), 'active disease' and 'drug intolerance'. Results: 463 patients were included; mean age was 51.1±21.6 years, with a 59.0% female predominance. Mean follow-up was 14.6±9.2 months. The most common diagnosis was dry eye disease (DED; 322, 69.5%), followed by allergic eye disease (AED; 53, 11.4%) and ocular mucous membrane pemphigoid/Steven-Johnson syndrome (OMMP/SJS; 38, 8.2%). Successful treatment was achieved in 343 (74.1%) patients, with 44 (9.5%) requiring additional treatment and 76 (16.4%) reporting drug intolerance. The efficacy of Ikervis was highest in DED (264, 82.0%), followed by OMMP/SJS (25, 65.8%) and post-keratoplasty (7, 50.0%; p<0.001). Logistic regression analysis demonstrated age <70 years (p=0.007), AED (p=0.002) and OMMP/SJS (p=0.001) as significant predictive factors for Ikervis intolerance. AED and post-keratoplasty were 8.16 times (95% CI, 2.78 to 23.99) and 13.98 times (95% CI, 4.22 to 46.28), respectively, more likely to require additional treatment compared with DED. Conclusions: Ikervis is a useful steroid-sparing topical treatment for managing OSIDs in the real-world setting. Preparations with improved tolerability are needed to benefit a larger number of patients.